Pension expectations and reality. What do Italian workers know about their future public pension benefits? - Massimo Baldini; Carlo Mazzaferro; Paolo Onofri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
We use 6 waves of the Bank of Italy's Survey on household income and wealth (SHIW) to check the evolution of workers' expectations on future pension benefits and retirement age from 2000 to 2012. Based on these two subjective evaluations, we compute a measure of expected pension benefit and compare it with a "true" measure of the same variable that we estimate on the basis of the pension rules in each year of the considered time lapse. By comparing subjective and "true" measures of the variable, we are able to measure the evolution over time of the "expectation error" and its distribution among different economic and demographic subsets of the population. Finally, we estimate a subjective measure of social security wealth and the degree of substitution between this variable and the private net worth of workers' households, in order to quantify the effects of pension reforms approved in the period considered on wealth accumulation.
Keywords: H55; D91; E21; 330